A retrospective observational study of tetralogy of fallot with pulmonary atresia and ductal-dependent pulmonary circulation focusing on the staged transannular patch procedure: a single-center study - Jae Hong Lee; Hyungtae Kim; Kwang Ho Choi; Si Chan Sung; Hyoung Doo Lee; Hoon Ko; Joung-Hee Byun; Tae Hong Kim; Mi Sook Yun (Journal of Cardiothoracic Surgery)
Abstract Background Management of pulmonary atresia with ventricular septal defect and ductal-dependent pulmonary circulation (PA/VSD/PDA) varies according to pulmonary artery morphology and institutional surgical strategy. We adopted a range of initial palliative surgical options for patients with PA/VSD/PDA and evaluated the effectiveness of our management strategy. Methods Twenty-five patients with PA/VSD/PDA were enrolled between May 2015 and July 2023. Patients with major aortopulmonary collateral arteries were excluded. The mean age at initial surgery was 14.9 ± 13.7 days, and the mean weight was 3.17 ± 0.35 kg. Twenty-two (88%) patients were neonates. Nineteen patients underwent initial palliative systemic-to-pulmonary shunt, while six underwent an initial definitive Rastelli operation depending on the main pulmonary artery morphology and branch pulmonary arteries size. Results One patient died of postoperative brain hemorrhage following the initial definitive Rastelli operation. The mean follow-up duration was 58.5 ± 28.4 months. During follow-up, one patient died suddenly two months after the initial central shunt procedure. All surviving patients with a shunt, except two, underwent biventricular repair: ten with the Rastelli operation and six with the transannular patch (TAP) procedure. The staged TAP group demonstrated a significantly larger freedom from reoperation rate than that of the initial Rastelli operation group (p = 0.022) and a significantly lower catheter-based reintervention rate than that of the other two management groups (p = 0.011). Conclusions A management strategy using an initial definitive Rastelli operation or systemic-to-pulmonary shunt based on main pulmonary artery development and branch pulmonary arteries size is safe and effective for PA/VSD/PDA treatment. The staged TAP procedure could be a viable option for patients with PA/VSD/PDA and a well-developed main pulmonary artery segment. Trial registration Not applicable.